2009
DOI: 10.1007/s00264-009-0781-6
|View full text |Cite
|
Sign up to set email alerts
|

Large bone distractor for open reconstruction of articular fractures of the calcaneus

Abstract: The results of operative treatment of two groups of patients with articular fractures of the calcaneus were evaluated. Twenty-three cases were treated surgically using a standard reconstruction procedure. In the second group of 19 patients a large bone distractor was used; it held the soft tissue flap retracted, while aiding in articular and tuberosity fragment reduction and increasing visualisation by distraction of the posterior talocalcaneal joint. After a year, the anatomical and functional results, togeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Surgeons in favor of bone grafting believe that it could stimulate fracture healing, leading to early full weight-bearing; may prevent posttraumatic arthritis; and could increase mechanical strength, thus helping to prevent significant late collapse [ 7 , 8 ]. Those not in favor of bone grafts have stated that the highly vascular calcaneus heals radiographically 4–8 weeks after surgery in the absence of bone grafting [ 9 11 ], that internal fixation can adequately support the articular surface, that bone grafting increases the infection rate, blood loss, and postoperative pain [ 12 , 13 ], and that it is also important to consider donor site morbidity and complications involved with harvesting an autograft [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Surgeons in favor of bone grafting believe that it could stimulate fracture healing, leading to early full weight-bearing; may prevent posttraumatic arthritis; and could increase mechanical strength, thus helping to prevent significant late collapse [ 7 , 8 ]. Those not in favor of bone grafts have stated that the highly vascular calcaneus heals radiographically 4–8 weeks after surgery in the absence of bone grafting [ 9 11 ], that internal fixation can adequately support the articular surface, that bone grafting increases the infection rate, blood loss, and postoperative pain [ 12 , 13 ], and that it is also important to consider donor site morbidity and complications involved with harvesting an autograft [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Orthopedic surgeons who insist on bone grafting believe it will stimulate fracture healing, leading to early full weightbearing, preventing posttraumatic arthritis, and increasing mechanical strength, and, thus, helping to prevent significant late collapse (13). Those who do not prefer bone grafting have suggested that internal fixation can adequately support the articular surface and that autografting could the infection rate, blood loss, postoperative pain, donor site morbidity, and complications (14)(15)(16)(17).…”
mentioning
confidence: 99%
“…The meta-analysis by Yang et al showed a mean AOFAS score in patients treated without bone graft to be 80.5 while the current study had a mean score of 81.7% [6] . [12] 38.8% 36.7% 13.2% 11.3% Grala et al (2009) [27] 26.2% 66.7% 0 7.1% Makki et al (2010) [15] 38.3% 36.2% 6.3% 19.2% Current study 22.2% 61.1% 16.7% 0…”
Section: Aofas Scorementioning
confidence: 98%